Baseline lymphocyte and cholinesterase levels may be the predictors of chronic herbal drug–induced liver injury - Zeng, Zhan; Yi, Wei; Dong, Jian-Ping; Chen, Qi-Qi; Sun, Fang-Fang; Lu, Hui-Hui; Lin, Yan-Jie; Bi, Xiao-Yue; Yang, Liu; Lu, Yao; Zhang, Lu; Li, Ming-Hui; et al. (Frontiers in Pharmacology, 2022)
ABSTRACT: Objective: To investigate the factors influencing the chronicity of drug-induced liver injury (DILI) caused by Chinese herbal medicine. Methods: Patients with DILI diagnosed by RUCAM score were enrolled retrospectively. The subjects were patients with DILI induced by taking Chinese herbal medicine, and were followed up for 48 weeks. These patients were divided into cure group and chronic group. The biochemical indicators were monitored at baseline and every 3 months. Logistic regression was used to analyze the risk factors of DILI chronicity. ROC (receiver operator characteristic, ROC) curve was used to analyze the diagnostic efficiency of each factor. Results: A total of 420 patients with DILI were enrolled, 122 of them were caused by Chinese herbal medicine, 70.5% of them were female (86/122), chronic group 39 (39/122, 31.97%), cure group 83 (83/122，68.03%); Cholinesterase (CHE) in the chronic group was lower than that in the cure group, (5467.10 ± 2010.40 U/L vs 6248..52±1901.78 U/L，p=0.04，t=2.078); There was no significant difference on the age between cured patients and chronic patients (p = 0. 156, Z = -1. 417). There was no significant difference between the prognosis of different genders (p = 0. 521, Z = -0. 639). Logistic regression analysis showed that baseline lymphocyte and cholinesterase were independent risk factors of drug induced chronicity (OR 0.429, 95%CI 0.205~0.898, P=0.025; OR 0.088, 95%CI 0.008~0.994, P=0.049). Conclusion: Baseline lymphocyte and cholinesterase may be the predictive factors for the chronicity of Chinese herbal medicine-induced liver injury. Keywords: drug-induced liver injury, herbal medicine, chronicity，predictor